Effect of functional feeds on fatty acid and eicosanoid metabolism in liver and head kidney of Atlantic salmon (Salmo salar L.) with experimentally induced Heart and Skeletal Muscle Inflammation - Martinez-Rubio, Laura; Morais, Sofia; Evensen, Oystein; Wadsworth, Simon; Vecino, Jose L G; Ruohonen, Kari; Bell, J Gordon; Tocher, Douglas R (Fish & Shellfish Immunology, 2013)
Heart and Skeletal Muscle Inflammation (HSMI) is an emerging viral disease caused by a novel Atlantic salmon reovirus (ASRV) affecting farmed fish. Primary symptoms associated with HSMI include myocardial and skeletal muscle necrosis indicating a severe inflammatory process. Recently, we applied the concept of clinical nutrition to moderate the long-term inflammatory process associated with HSMI in salmon subjected to experimental ASRV challenge. The use of functional feeds with lower lipid (hence energy) content reduced the inflammatory response to ASRV infection and the severity of associated heart lesions. The aim of the present study was to elucidate possible mechanisms underpinning the observed effects of the functional feeds, focussing on eicosanoid and fatty acid metabolism in liver and head kidney. Here we show that liver was also a site for histopathological lesions in HSMI showing steatosis reflecting impaired lipid metabolism. This study is also the first to evaluate the expression of a suite of key genes involved in pathways relating diet and membrane phospholipid fatty acid compositions, and the inflammatory response after ASRV infection. The expression of hepatic Δ6 and Δ5 desaturases was higher in fish fed the functional feeds, potentially increasing their capacity for endogenous production and availability of anti-inflammatory EPA. Effects on mobilization of lipids and changes in the LC-PUFA composition of membrane phospholipids, along with significant changes in the expression of the genes related to eicosanoid pathways, showed the important role of the head kidney in inflammatory diseases caused by viral infections. The results from the present study suggest that clinical nutrition through functional feeding could be an effective complementary therapy for emerging salmon viral diseases associated with long-term inflammation.